2012
DOI: 10.1038/emboj.2012.289
|View full text |Cite
|
Sign up to set email alerts
|

CHD1 remodelers regulate nucleosome spacingin vitroand align nucleosomal arrays over gene coding regions inS. pombe

Abstract: Nucleosome positioning governs access to eukaryotic genomes. Many genes show a stereotypic organisation at their 5 0 end: a nucleosome free region just upstream of the transcription start site (TSS) followed by a regular nucleosomal array over the coding region. The determinants for this pattern are unclear, but nucleosome remodelers are likely critical. Here we study the role of remodelers in global nucleosome positioning in S. pombe and the corresponding changes in expression. We find a striking evolutionary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
94
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 102 publications
6
94
1
3
Order By: Relevance
“…In addition, depletion of histone H3 proteins in S. cerevisiae also results in alterations in nucleosome occupancy and positions at a defined subset of nucleosomes, and interestingly, nucleosomes altered by H3 depletion do not overlap with those altered in cells lacking Nhp6a/Nhp6b (61). Schizosaccharomyces pombe cells lacking chromatin remodeler Chd1 (Hrp3 in S. pombe) exhibit global changes in nucleosomes and production of antisense transcripts (62)(63)(64). Finally, S. pombe yeast cells lacking histone chaperone Spt6 also exhibit dramatic changes in nucleosome positioning and occupancy and increased cryptic transcription (65).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, depletion of histone H3 proteins in S. cerevisiae also results in alterations in nucleosome occupancy and positions at a defined subset of nucleosomes, and interestingly, nucleosomes altered by H3 depletion do not overlap with those altered in cells lacking Nhp6a/Nhp6b (61). Schizosaccharomyces pombe cells lacking chromatin remodeler Chd1 (Hrp3 in S. pombe) exhibit global changes in nucleosomes and production of antisense transcripts (62)(63)(64). Finally, S. pombe yeast cells lacking histone chaperone Spt6 also exhibit dramatic changes in nucleosome positioning and occupancy and increased cryptic transcription (65).…”
Section: Discussionmentioning
confidence: 99%
“…S6). However, similar to Chd1-null strains of Saccharomyces cerevisiae and Schizosaccharomyces pombe (Hennig et al, 2012;Pointner et al, 2012), initial microarray analyses showed very few genes changing in expression in Chd1 −/− ESCs (data not shown). Although we had previously reported that Chd1 RNAi ESCs upregulated genes of the neural lineage (Gaspar-Maia et al, 2009), we subsequently found that this could be suppressed by high doses of commercially available leukemia inhibitory factor (LIF) (data not shown), the conditions we currently use (see Materials and Methods).…”
Section: Chd1mentioning
confidence: 99%
“…Chromatin remodelers are multiprotein complexes that use ATP hydrolysis to facilitate the sliding, eviction or histone exchange of nucleosomes (Clapier and Cairns 2009). Remodelers show different specificity and directionality in their mode of action (Stockdale et al 2006;Yen et al 2012), and the removal of some of them, like Hrp3 in Schizosaccharomyces pombe (Hennig et al 2012;Pointner et al 2012;Shim et al 2012) or Isw1 and Chd1 in Saccharomyces cerevisiae (Gkikopoulos et al 2011), results in gross genome-wide alteration of their nucleosomal patterns.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%